Electronics projects with the ESP8266 and ESP32 : building web pages, applications, and Wifi enabled devices - Cameron, Neil (Technology in action series., 2021)
Discover the powerful ESP8266 and ESP32 microcontrollers and their Wi-Fi communication. The ESP32 microcontroller features Bluetooth and BLE communication in addition to Wi-Fi. The book emphasizes practical projects and readers are guided through Wi-Fi and Bluetooth communication, mobile app design and build, ESP-NOW and LoRa communication, and signal generation. Projects throughout the book utilize the Wi-Fi functionality and processing power of the ESP microcontrollers. Projects are built in the Arduino IDE, so you don't need to download other programming software. Mobile apps are now ubiquitous, making the app build projects of the book very relevant, as are the web page design projects. In Electronics Projects with the ESP8266 and ESP32, you'll see how easy and practical it is to access information over the internet, develop web pages, build mobile apps to remotely control devices with speech recognition or incorporate Google Maps in a GPS route tracking app. You will · Build practical electronics projects with an ESP8266 or ESP32 microcontroller with Wi-Fi communication · Use the Wi-Fi function of the ESP8266 and ESP32 to update web pages · Communicate with your mobile phone or smart watch by Bluetooth Low Energy · Transmit and receive information to control remote devices over the internet · Understand the design and build of mobile apps for internet based applications · Apply your computer programming skills in C++, JavaScript, AJAX and JSON · Use WebSocket, MQTT brokers and IFTTT for fast two-way communication with webpages.